PERENCANAAN ULANG BENDUNG DAGELONGGA –DESA KORO BHERA - KECAMATAN MEGO – KABUPATEN SIKKA - Boro Bebe Fransiskus Xaverius; Dedi Imanuel Pau; Maria Kurniaty Lete (Program Studi Teknik Sipil, 2025)
The Dagelongga Dam was built in 2003 and was completely damaged by flooding in 2021. This study aimed to calculate the planned flood discharge and to technically redesign the Dagelongga Dam so that it could irrigate all rice fields. The study was conducted in the Kali Wajo River, Koro Bhera Village, Mego District, Sikka Regency, which is also the planned location for the Dagelongga Dam reconstruction. The study involved measuring and collecting data at the research location, as well as collecting relevant data on the dam planning, such as rainfall and general watershed data. The results of the study in the form of hydrological analysis with the results of the calculation of the planned flood discharge for a 25-year return period (Q25) of: 199, 822 m3/sec and the results of the re-planning design of the Dagelongga dam obtained: total width of the dam: 29 m, total width of the flushing building 4.5 m, planned to use 2 (two) flushing buildings, with 1 (one) building being an existing building with a width of 1 m, and 1 (one) new flushing building with a width of 1.5 m, Dam height: 1.5 m, with a weir crest elevation of + 53.8 m and a river bed elevation of + 52.3 m, the type of weir crest is a round crest with a radius of curvature of the crest (r) = 0.8 m, the length of the stilling basin floor: 5 m, with a stilling basin base elevation: +50.15 m and using a